PRODUCTION FACILITY LAYOUT STUDY OF COSMETIC FACTORY - Yulianti, Yuli
Indonesia cosmetic market's growth continously increase, the sales is IDR 61.46 trillion or growing by 6.6% compare to 2018, and is predicted consistently increase every year of around 4.2% (CAGR 2019-2023). To fulfill market needs, PT X will increase production capacity by establishing new factory facilities in different location. Layout and machinery facilities strongly affect the eficiency and productivity of factory. With quantitative descriptive method, this research aims to provide a study and assess the effectiveness of the planning layout design, as well as an evaluation of the requirement and the placement of production machinery facilities to achieve the specified production targets. An effective layout can reduce material handling cost. After going through 5 iterations of room exchange using the CRAFT (Computerized Relative Allocation of Facilities Tehnique) algorithm, the most effective layout proposal is obtained with a reduction in the cost of yearly handling material from IDR. 405,684,990,- to IDR. 328,918,860, -, or cost efficiency of 18.92%. The effectiveness of the layout is also measured through the number of closeness gap (CG), where the initial layout has a closeness gap value of 0.47 and changes in the final layout proposal to 0.40, or decreased by 16.08%. Thus the proposed layout is proven to be more effective than initial layout, thus can optimize factory productivity.